Do Digital Capabilities, Business Process Automation, and Agile Mindset Significantly Affect The Operational Effectiveness of Technology Startups in South Jakarta? - Salwa Aulia Novitasari; Zainal Arifin; Muhamad Ammar Muhtadi (West Science Interdisciplinary Studies, 2026)
The rapid development of digital technology has transformed the operational landscape of technology startups, requiring organizations to enhance their efficiency and adaptability in highly competitive environments. This study aims to analyze the influence of digital capabilities, business process automation, and agile mindset on the operational effectiveness of technology startups in South Jakarta. A quantitative research approach was employed using survey data collected from 125 respondents working in technology startup companies. The data were gathered through structured questionnaires measured using a five-point Likert scale and analyzed using multiple linear regression with SPSS version 25. The results of the analysis show that digital capabilities, business process automation, and agile mindset have positive and significant effects on operational effectiveness. Digital capabilities were found to improve organizational efficiency through the effective use of digital technologies and data-driven decision-making. Business process automation contributes to operational efficiency by reducing manual processes and increasing workflow consistency. Meanwhile, an agile mindset enhances organizational flexibility, enabling startups to respond quickly to market changes and technological developments. The simultaneous testing results also indicate that these three variables collectively explain a significant proportion of operational effectiveness in technology startups. The findings suggest that the integration of digital capabilities, automation technologies, and agile organizational culture plays a crucial role in strengthening the operational performance of technology startups. This study provides practical insights for startup managers and policymakers in developing strategies that support digital transformation and sustainable operational growth.